2019
DOI: 10.1101/732263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Th22 cells are a major contributor to the mycobacterial CD4+ T cell response and are depleted during HIV infection

Abstract: 41HIV-1 infection substantially increases the risk of developing tuberculosis (TB). Some 42 mechanisms, such as defects in the Th1 response to Mycobacterium tuberculosis (M.tb) in 43HIV-infected individuals have been widely reported. However, Th1-independent mechanisms 44 also contribute to protection against TB. To identify a broader spectrum of defects in TB 45 immunity during HIV infection, we examined IL-17 and IL-22 production in response to 46 mycobacterial antigens in individuals with latent TB infectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 68 publications
6
15
0
Order By: Relevance
“…IL-22 has been classified as a Th17 cytokine due to co-expression with IL-17 in mouse studies and several shared functions between the two cytokines (39). Consistent with previous studies (29,31), our results showed that the vast majority of IL-22 is produced independently of IL- In accordance with previous data (25), we show that Mtb-specific Th22 responses in the blood were 50% lower in individuals with TB compared to Mtb-exposed individuals. It is likely that in the context of TB disease, Mtb-specific Th22 cells migrate to the lungs.…”
Section: Tb Disease and Hiv Co-infection Differentially Influence Memsupporting
confidence: 92%
See 2 more Smart Citations
“…IL-22 has been classified as a Th17 cytokine due to co-expression with IL-17 in mouse studies and several shared functions between the two cytokines (39). Consistent with previous studies (29,31), our results showed that the vast majority of IL-22 is produced independently of IL- In accordance with previous data (25), we show that Mtb-specific Th22 responses in the blood were 50% lower in individuals with TB compared to Mtb-exposed individuals. It is likely that in the context of TB disease, Mtb-specific Th22 cells migrate to the lungs.…”
Section: Tb Disease and Hiv Co-infection Differentially Influence Memsupporting
confidence: 92%
“…A subset of CD4+ T cells that produces the cytokine IL-22 in response to mycobacterial antigen stimulation has been described (29)(30)(31). We sought to further characterize Mtb-specific IL- repertoire coverage for Mtb-specific IL-22-producing CD4+ T cells was broad and comparable to total CD4+ T cells, while slightly lower coverage was observed for Mtb-specific IFN- producing CD4+ T cells (medians 62%, 61% and 40%, respectively).…”
Section: Characterization Of Cd4 Th22 Cells In the Immune Response Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In non-human primates, IL-22 mRNA expression was reduced in peripheral blood of Mtb-infected monkeys but increased in lung lymphocytes, bronchial lymph nodes, and spleen, suggesting a role for IL-22 in lymphoid and lung tissues 60 . Finally, several studies have reported IL-22 expression after BCG stimulation of whole blood from individuals living in settings endemic for TB 46,[61][62][63] . Interestingly, IL-22-expressing cells are not readily detected after stimulation of PBMC or in response to peptides 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several studies have reported IL-22 expression after BCG stimulation of whole blood from individuals living in settings endemic for TB 46,[61][62][63] . Interestingly, IL-22-expressing cells are not readily detected after stimulation of PBMC or in response to peptides 61 . This technical observation has important implications for studies that seek to determine if IL-22 is a correlate of protection, since such studies are typically done on cryopreserved PBMC.…”
Section: Discussionmentioning
confidence: 99%